Manganese Mobility in Gale Crater, Mars: Leached Bedrock and Localized Enrichments. Issue 10 (6th October 2022) - Berger, J. A.; King, P. L.; Gellert, R.; Clark, B. C.; Flood, V. A.; McCraig, M. A.; Ming, D. W.; O'Connell‐Cooper, C. D.; Schmidt, M. E.; Thompson, L. M.; VanBommel, S. J. V.; Wilhelm, B.; et al.
Abstract: In Gale crater on Mars, the rover Curiosity has discovered evidence of fluid mobilization of the redox‐sensitive element manganese. We present results for Mn from Curiosity 's Alpha Particle X‐ray Spectrometer (APXS), which show that the average MnO concentration in mudstone‐dominated sedimentary units (0.22 wt%) is about one‐half of the concentration in the average Mars crust (0.44 wt%). Geochemical trends indicate that Mn in the sedimentary bedrock, most of which has a basaltic provenance, was leached by chemical alteration and dissolution. In >350 vertical meters of mudstone‐dominated strata, the apparent leaching of Mn and retention of Fe in Fe‐O‐H phase(s) resulted in the fractionation of Fe and Mn, indicating relatively moderate Eh‐pH fluid conditions that were not highly alkaline, reducing, or oxidizing. Exceptions are fracture‐associated, silica‐rich haloes where both Mn and Fe were leached by low pH fluids. The rover also discovered Mn‐rich veins, nodules, and patchy, dark coatings on rock surfaces, which are variably associated with enrichments in Fe, P, Cl, and/or Zn. These Mn‐rich features represent ∼1% of the 1029 APXS measurements acquired over ∼25 km of rover traverse. A thermochemical model shows that dissolved Mn 2+ could have been concentrated via evaporation, sublimation, and/or freezing. Manganese was then likely precipitated in localized features when >99.99% of the Mn 2+ ‐bearing water was removed from the system. These findings indicate that Mn was mobile in Gale crater and therefore bioavailable as a potential energy source for life. Plain Language Summary: In Gale crater on Mars, the rover Curiosity has discovered evidence of the mobility of the redox‐sensitive element manganese. We present results for manganese analyses from Curiosity 's Alpha Particle X‐ray Spectrometer, an instrument that measures the elemental compositions of martian materials. In most of the layered sedimentary bedrock, manganese concentrations are about one‐half of the average Mars crustal composition (approximated as basaltic soil). Our interpretation of the manganese‐depleted bedrock is that the element was leached by chemical processes involving water. In most of the bedrock, manganese was likely removed in fluids, whereas iron was not, indicating that this occurred under relatively moderate aqueous conditions. The rover has also discovered manganese‐rich veins, nodules, and dark coatings on rock surfaces. These manganese‐rich features are associated with enrichments in iron, phosphorus, chlorine, and/or zinc. We provide a thermochemical model to support the hypothesis that the reduced form of manganese (Mn 2+ ) could have been dissolved in water and concentrated as the water evaporated. Manganese was then deposited in localized features when >99.99% of the Mn 2+ ‐bearing water was removed by evaporation. These findings indicate that manganese was dissolved in Gale crater water and was accessible as a potential chemical energy source for life. Key Points: In Gale crater on Mars, manganese is depleted in bedrock and enriched in nodules, veins, and coatings Manganese was likely leached by aqueous chemical alteration and concentrated in solution via evaporative brine evolution and diagenesis Manganese and iron fractionation in mudstone counterindicates highly alkaline, reducing, and/or oxidizing fluid conditions